RESIDU PESTISIDA PIRETROID PADA BAWANG MERAH DI DESA SRIGADING KECAMATAN SANDEN KABUPATEN BANTUL - Iin Narwanti; Eko Sugiharto; Chairil Anwar (Universitas Ahmad Dahlan, 2012)
Pyrethroid pesticide residue in onion from Srigading Village, Sanden District,Bantul Regency has been investigated. The purpose of this study were to analyze,identificate and evaluate pyrethroid pesticide residues in onion. Onion sample wasextracted using homogenizer with acetone solvent. Clean-up was done usingchromatography column using florisil and determination of pesticide residue in thesamples was carried out by gas chromatography apparatus equipped with electroncapture detector (GC-ECD). The result showed that pesticide residues in onion samplein the range level: -cypermethrin (98.8-245.6 ppb) and -cyhalothrin (14.4-120.0ppb). The following pesticides have been detected in some of samples of onion analysed,but they have been detected above the Maximum Residue Limit (MRL).